Aprendizaje Cooperativo Como Estrategia Pedagógica Para El Manejo De Residuos Sólidos Con Estudiantes De Quinto Grado De La Institución Educativa Robledo- Sede Simón Bolívar, Calarcá, Quindío (2013)
Cooperative learning refers to an alternative way of organizing the cognitive processes that are to result in a process of learning both inside and outside the classroom. This term refers to teamwork methodologies that drive the group to cooperate towards a common goal. That is, it comes with its implementation to overcome certain "gaps" produced with the exclusive application of traditional techniques of group learning, more concerned that yields results, group rather than individual responsibilities, heterogeneous rather than homogeneous groups, leaders rather unique of shared leadership. This work shows six teaching strategies to encourage cooperative learning about solid waste management with students of fifth grade. Using these strategies serves a dual purpose, first teach students to engage, interact and work together, and otherwise prepare to begin a conceptual shift on solid waste management contributing to the care of medium conservation. This project is a qualitative study with a quasi-experimental design (pretest and posttest), focused on a group of thirty-two (32) students OF SCHOOL ROBLEDO- SEDE SIMON BOLIVAR, CALARCÁ, QUINDÍO.